2022
DOI: 10.1021/jacs.1c12174
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Photoenolization-Driven Cycloadditions Using Theory and Spectroscopy

Abstract: The first broad spectrum investigation into the photoenolization/Diels-Alder (PEDA) sequence was carried out using M06-2X/6-31+G(d,p) in conjunction with SMD solvation and supported by experimental UV−vis spectroscopy. A test set of 20 prodienes was chosen to examine the role of the H atom acceptor group (substituted and unsubstituted carbonyl, thiocarbonyl, and imine), the H atom donor group, and bystander ring substituents. As reaction partners for the photogenerated dienes, a diverse test set of 20 dienophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…The combination of M06-2X and SMD models has been demonstrated to be accurate for organic reactions in polar solvents. 23 3D structures were prepared using the CYLview 1.0 program. 24…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of M06-2X and SMD models has been demonstrated to be accurate for organic reactions in polar solvents. 23 3D structures were prepared using the CYLview 1.0 program. 24…”
Section: Methodsmentioning
confidence: 99%
“…Solvation was included using the SMD implicit solvation model and THF as a solvent, which is used experimentally in the aza-Piancatelli reaction. The combination of M06-2X and SMD models has been demonstrated to be accurate for organic reactions in polar solvents . 3D structures were prepared using the CYLview 1.0 program…”
Section: Methodsmentioning
confidence: 99%
“…Photochemically induced [4 + 2] cycloadditions can be achieved by photoenolization of o MBA and subsequent Diels–Alder reaction with electron-deficient dienophiles. Mechanistically, the 1,5-hydrogen atom transfer taking place on the triplet manifold leads to a ( Z )-enol, constituting a highly reactive diene. When alkynes are used as dienophiles, the initially formed non-fluorescent 1,4-dihydro-1-naphthole cycloadduct can be quantitatively converted to the respective fluorescent naphthalene via E1-elimination in the presence of catalytic amounts of acid.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Coote and co-workers theoretically investigated the role of substituents and dienophiles and found that the reaction is tolerant of most substitutions, critically broadening the potential synthetic toolbox. 27 PEDA reactions where each enolization system can be accessed with a unique wavelength are fascinating enities, opening the door to modify and implement this efficient reaction into complex molecular structures. Indeed, we recently introduced unsymmetric methylisophthalaldehydes (MIAs), which undergo two wavelength-gated PEDA reactions to form heterobifunctional adducts.…”
Section: ■ Introductionmentioning
confidence: 99%